DFT Prediction of Structural and Physical Properties of Cr3AlC2 Under Pressure - Jianhui Yang; Shenghai Fan; Haijun Hou; Qiang Fan (Nanomaterials)
This work explores the physical properties of the MAX-phase material Cr3AlC2 through the application of density functional theory (DFT). The refined lattice parameters were determined through the minimization of the total energy. In order to explore the electronic properties and bonding features, we carried out computations on the band structure and charge density distribution. The calculated elastic constants (Cij) validated the mechanical stability of Cr3AlC2. To assess the material’s ductility or brittleness, we calculated Pugh’s ratio, Poisson’s ratio, and Cauchy pressure. The hardness was determined. This study examined the anisotropic behavior of Cr3AlC2 using directional analyses of its elastic properties and by computing relevant anisotropy indicators. We examined several key properties of Cr3AlC2, including the Grüneisen parameter, acoustic characteristics, Debye temperature, thermal conductivity, melting point, heat capacity, Helmholtz free energy, entropy, and internal energy. Phonon dispersion spectra were analyzed to assess the dynamic stability of Cr3AlC2.